Monster of the twentieth century Kōtoku Shūsui and Japan's first anti-imperialist movement - Tierney, Robert Thomas 1953- (University of California Press, 2015)
"This extended monograph examines the work of the radical journalist Kōtoku Shūsui and Japan's anti-imperialist movement of the early twentieth century. It includes the first English translation of Kotoku Shusui's classic 1901 work Teikokushugi (Imperialism). Shūsui was a Japanese socialist, anarchist, and critic of Japan's imperial expansionism who was executed in 1911 for his alleged participation in a plot to kill the Emperor. Imperialism was one of the first systematic criticisms of imperialism published anywhere in the world. In this seminal text, Shūsui condemns global imperialism as the commandeering of politics by national elites and denounces patriotism and militarism as the principal causes of imperialism. In addition to the translation, author and translator Robert Tierney offers an in-depth study of Shūsui's text and of the early anti-imperialist movement he led. Tierney's study places Shūsui's book within the broader context of early twentieth-century debates on the nature and causes of imperialism. It also offers a detailed account of the different stages of the Japanese anti-imperialist movement. Monster of the Twentieth Century constitutes a major contribution to the intellectual history of modern Japan and to the comparative study of critiques of capitalism and colonialism."--Provided by publisher.